Cooperation challenges in agricultural cooperatives - Leite, Amanda Regina; Padilha, Ana Claudia Machado; Binotto, Erlaine (Revista de Administração da UFSM, 2021)
Objective – This paper aimed to understand the elements in cooperative arrangements of agribusiness that facilitate and hinder cooperation. Design/methodology/approach -A descriptive research was carried out based on the 50 questionnaires applied to farmers´ members of cooperatives in Rio Grande do Sul, Brazil. Results - Results indicated that farmers are increasingly expanding their role in making productive activities possible through cooperation promoted by cooperatives. Better access to information, sales opportunities, technical assistance, and, mostly, a favorable environment for the exchange of knowledge are the main responsible facts. As for cooperation, the relationship of trust established between cooperative members and cooperatives stands out, as well as the fidelity of membership that sustains the system, which can be weakened by opportunistic actions that may affect the continuity and fulfillment of the cooperatives’ objectives over time. Cooperative relationship face to competition is a good alternative for promoting the achievement of objectives by farmers that would be challenging or impossible in isolation. Originality - The cooperation promoted by cooperative organizations, broadens the understanding that by joining forces they can enter restricted markets. This occurs especially when it comes to the studied farmers – different sizes and patterns of production and activities that are constantly under economic and financial pressure.